(untitled) (International Association of Biologicals and Computational Digest, 2022)
Achyranthes aspera L. belonging to the family Amaranthaceae commonly known as ‘Aghedo’ is an important medicinal herb found as a weed throughout India. The whole plant is of immense importance because of a wide range of pharmacological actions. Hence, the present study was undertaken to identify the functional groups present within the leaves. The FT-IR results showed the presence of 11 peaks, which confirmed the presence of essential phytochemicals present in the crude sample of powdered A.aspera leaves.